2022
DOI: 10.1109/tse.2022.3140230
|View full text |Cite
|
Sign up to set email alerts
|

How Can Human Values Be Addressed in AgileMethods A Case Study on SAFe

Abstract: Agile methods are predominantly focused on delivering business values. But can Agile methods be adapted to effectively address and deliver human values such as social justice, privacy, and sustainability in the software they produce? Human values are what an individual or a society considers important in life. Ignoring these human values in software can pose difficulties or risks for all stakeholders (e.g., user dissatisfaction, reputation damage, financial loss). To answer this question, we selected the Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Our presentation of the findings follows a style common to reporting the findings of similar case studies in software engineering, e.g. [6], [63]. Details on the data collection and analysis are presented in sections 3.2 and 3.3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our presentation of the findings follows a style common to reporting the findings of similar case studies in software engineering, e.g. [6], [63]. Details on the data collection and analysis are presented in sections 3.2 and 3.3.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure a systematic and rigorous research process, we employed a range of quality assurance procedures. In the following, we review some of the study's potential limitations in relation to the quality criteria of credibility, transferability, and confirmability [84] that is much used in interpretive and constructivist qualitative research, including in the software engineering field, e.g., [63], [86].…”
Section: Limitations and Evaluationmentioning
confidence: 99%
“…implementation). For example, Hussain et al have identified several places to introduce values throughout the software development phases in the SAFe Agile framework (Hussain et al 2022). In addition, these works proposed solutions as methods or frameworks.…”
Section: Solutions To Integrate Values In Softwarementioning
confidence: 99%
“…Whittle et al argued for the consideration and inclusion of human values at different stages in the software development life cycle [54]. Another study introduced a set of interventions for addressing human values in the SAFe Agile framework [55]. Other related works have proposed tools for supporting human values, e.g., a human values dashboard for software development [56], values Q-sort -an instrument for capturing the values of software engineers [57], and algorithms for detection the violation of values in Android APIs [16].…”
Section: Human Aspects In Software Developmentmentioning
confidence: 99%